Sexual and reproductive health and rights and climate change about menstrual discrimination: a policy review in the context of Nepal - Paudel, Radha; Acharya, Devaraj; Adhikari, Tejaswi Mili (Frontiers in Global Women's Health, 2025)
The conversation around climate, sexual and reproductive health and rights (SRHR), and menstruation is increasing more than ever in Nepal. The discussion between climate and SRHR is more visible and it endeavors to develop the relationship between them. The claim of the role of menstrual discrimination (MD) is the construction and reinforcement of power and patriarchal demands unveiling MD as an underlying barrier for gender-responsive climate or SRHR interventions. In this vein, this study reviewed the national policies of climate change (CC) and SRHR with MD. It aims to examine the positioning of MD in ongoing policies around SRHR and CC. It is crucial to accelerate the impact of interventions related to SRHR and CC to achieve broader gender justice and human rights. The policy-related documents regarding CC and SRHR are reviewed. The visible and invisible MD is rampant across the country regardless of class, caste, region, or religion. The Government of Nepal started to work on SRHR in 2000, although the specific policies on dignified menstruation were made in 2017. MD is missed across all the conversations of CC although it talks about gender equality and social inclusion policies (GESI). The GESI policies and programs do not spell out the discrimination related to menstruation and its impact throughout life, and the SRHR policy has a similar impact. MD is one of the missing dimensions regarding power relations, patriarchy, climate, and SRHR. This study recommends a thorough unpacking of MD, including its impact, incorporating the strategies to dismantle MD in both SRHR and ensuring CC-related policies and programs for real equality and inclusion. The findings of this research become helpful to policymakers during intervention planning to overcome the situation.